Discovering the perceived social support, needs, and friendships of an Irish online support group throughout the first two years of the Coivd-19 pandemic - Conor Hogan (International Journal of Medical Toxicology and Legal Medicine, 2024)
When masses of people become aware of life changing events panic can set in for many and support is required. In the early months of 2020 the Covid-19 began and the virus spread around the world in a rapid time. Many people sought out support so that they could feel better and adapt their lives to the new form of daily living. These are the realities of what occurred throughout the world in 2020 and were observed within the online Facebook group entitled the Irish Self Isolation Support group. This paper seeks to establish the perceived social support, needs, and friendships of an Irish online support group throughout the duration of the Coivd-19 pandemic. The members of the group are all adults and come from all over Ireland. In all, there are nearly 3,442 members of the group and the members came from 32 different counties. By learning from the experiences of this online support group other online support groups can plan to improve their practices to help others around the world when times of unprecedented global challenges occur and peoples’ daily lives are suddenly altered. The results of this study from the research within the Facebook group show that although the majority of participants in the group were very positive and supportive of all other group members throughout the early years of the pandemic they also became disinterested in supporting others online once vaccines became available to the general public in most developed countries. However, some friendships were made throughout the pandemic within the group and remain to this day.